Achieving Equity in Emergency Medicine Quality Measures Requires a Sex and Gender Lens - Thomas, Ynhi T.; Jarman, Angela F.; Faynshtayn, Nina G.; Buehler, Greg B.; Andrabi, Sara; McGregor, Alyson J. (The Journal of emergency medicine, 2023)
Quality measures within Emergency Medicine (EM) were developed to standardize and improve care. Their development has been limited by lack of consideration of sex- and gender-based differences. Research has suggested that sex and gender can impact clinical care and treatment. Inclusion of sex and gender differences is needed to create EM quality measures that are equitable to all. The aim of the review is to provide a brief history of EM quality measures and the value of considering sex- and gender-based evidence in their development to ensure equity, using acute myocardial infarction (AMI) as an example. Current quality measures related to AMI, such as time-to-electrocardiogram and door-to-balloon time in percutaneous coronary intervention, may have important and modifiable disparities when stratified by sex. Even when presenting with signs and symptoms of AMI, women experience delayed time to diagnosis and treatment. Few studies have considered interventions to mitigate these differences. However, the data available suggest that sex-based disparities can be minimized by implementation of strategies such as a quality control checklist. Quality measures were created to deliver high-quality, evidence-based, and standardized care, but without the inclusion of sex and gender metrics, they may not advance care to an equitable level.